2018
DOI: 10.1016/j.ymthe.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Long-Term Efficacy of AAV4 Gene Therapy in Patients with RPE65 Leber Congenital Amaurosis

Abstract: The aim of this study was the evaluation of the safety and efficacy of unilateral subretinal injection of the adeno-associated vector (AAV) serotypes 2 and 4 (AAV2/4) RPE65-RPE65 vector in patients with Leber congenital amaurosis (LCA) associated with RPE65 gene deficiency. We evaluated ocular and general tolerance and visual function up to 1 year after vector administration in the most severely affected eye in nine patients with retinal degeneration associated with mutations in the RPE65 gene. Patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 40 publications
1
62
0
1
Order By: Relevance
“…In the treatment of retinal diseases such as Leber congenital amaurosis, AAV is a widely utilized platform for therapeutic gene delivery and has demonstrated long-term efficacy and safety. [23][24][25] Intravitreally administered AAVs do not significantly affect the gene expression in other organs. [26][27][28] Similarly, both AAV-CjCas9: Vegfa and Hif1a did not induce any change in body weights of treated mice, regardless of their local effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of retinal diseases such as Leber congenital amaurosis, AAV is a widely utilized platform for therapeutic gene delivery and has demonstrated long-term efficacy and safety. [23][24][25] Intravitreally administered AAVs do not significantly affect the gene expression in other organs. [26][27][28] Similarly, both AAV-CjCas9: Vegfa and Hif1a did not induce any change in body weights of treated mice, regardless of their local effects.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy represents a promising therapeutic option for many inherited diseases, as has been recently demonstrated for genetic immunodeficiencies, hemophilia, inherited blindness, or spinal muscular atrophy . Those studies have demonstrated that selection of the proper vector is key for success of the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, management of most forms of LCA/EOSRD has been symptomatic, but the previous decade has brought major scientific advances leading to a major breakthrough in the treatment of the specific form associated with mutations in the RPE65 gene. A total of five phase 1/2 gene replacement therapy trials [23][24][25][26][27] have shown that subretinal injection of a recombinant AAV2 vector containing the RPE65 cDNA is safe and can substantially improve retinal function based on measurements of visual acuity, dark-adapted perimetry, dark-adapted full-field sensitivity testing, static 30-degree perimetry, kinetic perimetry visual field area, as well as cortical activation along visual pathways measured by fMRI techniques. The phase 3 trial of subretinal administration of an AAV2/2 vector reported clinically meaningful and statistically significant benefit at 1 year, reaching its primary end point for efficacy with improved performance on standardized multiluminance mobility testing (MLMT).…”
Section: Leber's Congenital Amaurosis/early-onset Severe Retinal Dystmentioning
confidence: 99%